Bacteria clustering by polymers induces the expression of quorum sense controlled phenotypes - Lui, Leong T.; Xue, Xuan; Sui, Cheng; Brown, Alan; Pritchard, David I.; Halliday, Nigel; Winzer, Klaus; Howdle, Stephen M.; Fernandez-Trillo, Francisco; Krasnogor, Natalio; Alexander, Cameron (Nature Publishing Group, 2013)
Bacteria deploy a range of chemistries to regulate their behaviour and respond to their environment. Quorum sensing is one mean by which bacteria use chemical reactions to modulate pre-infection behaviour such as surface attachment. Polymers that can interfere with bacterial adhesion or the chemical reactions used for quorum sensing are thus a potential means to control bacterial population responses. Here we report how polymeric "bacteria sequestrants", designed to bind to bacteria through electrostatic interactions and thus inhibit bacterial adhesion to surfaces, induce the expression of quorum sensing controlled phenotypes as a consequence of cell clustering. A combination of polymer and analytical chemistry, biological assays and computational modelling has been used to characterise the feedback between bacteria clustering and quorum sensing signaling. We have also derived design principles and chemical strategies for controlling bacterial behaviour at the population level